Molecular Mechanisms of PPAR-γ Governing MSC Osteogenic and Adipogenic Differentiation - Zhuang, Haoliang; Zhang, Xu; Zhu, Chuntie; Tang, Xiaoshan; Yu, Fang; wei Shang, Guang; Cai, Xiaoxiao (Current Stem Cell Research & Therapy, 2016)
Sharing the same precursor cell lineage located in the bone marrow, mesenchymal stroma/stem cells (MSCs), osteoblasts and adipocytes have a reciprocal relationship in differentiation and function. The nuclear transcription factor peroxisomeproliferator- activated receptor-gamma (PPAR-γ) has been found expressed in both osteoblasts and adipocytes, as well as in MSCs, suggesting its crucial role in regulating adipocyte formation and osteoblast development. It has been observed in animal models that upregulated PPAR-γ activity results in bone loss where marrow adiposity is facilitated, while downregulated PPAR-γactivity leads to bone mass elevation. Evidence suggests that the dual function of PPAR-γ in either anti-osteoblastic or pro-adipocytic aspects is determined by its ligand. Furthermore, various cytokines and extracellular signaling pathways are involved in the transactivation of PPAR-γ, which can trigger the adipogenesis/osteoblastogenesis switch. PPAR-γ, therefore, shows tremendous potential in novel strategies for bone tissue engineering and clinical application. This review summarizes the regulatory function of PPAR-γ in MSC differentiation, as well as the cytokine and extracellular signaling pathways participating in the cross-talk between adipogenesis and osteoblastogenesis.
Keywords: PPAR-γ